THE ROLE OF TRANSPARENCY STANDARD: EFFECTIVITY IN PROVING THE BREACH OF FAIR AND EQUITABLE TREATMENT - Musu, Clara; Trisnamansyah , Purnama (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2024)
The existence of agreements in foreign investment does not avoid disputes that occur in foreign investment agreements so there is a dispute resolution mechanism known as investor-state dispute settlement (ISDS). One of the claims often used as the basis for ISDS claims is the Fair and Equitable Treatment (FET) principle. In practice, investors often fail to prove violations due to lacking elements in their proof. The transparency standard is one of the elements that can support investors in proving the violations. In practice, transparency standards are rarely used to prove violations of the FET principle because there are still no clear parameters regarding implementing these standards and what kind of transparency standards can be said to violate the FET principle. The purpose of this study is to determine the role of transparency standards in their position as part of the FET principle and to determine the effectiveness of transparency standards in proving violations of FET in ISDS practices. The research method used in writing this thesis is to take a normative juridical approach by studying and examining secondary data in the form of international arbitration case jurisprudence, bilateral agreements, and international customs. The data is collected through literature studies obtained from primary and secondary data, which are then analyzed qualitatively. Based on the results of this study, it can be concluded that transparency standards have a protective role for investors and host states as an instrument to resolve legal uncertainty about existing decisions and policies and as a basis for analytical considerations to distinguish between legitimate regulatory actions and takeover actions that can indirectly violate the FET principle. Nonetheless, the Tribunal did not explicitly mention the transparency standard, but it was effectively used as a basis for arguments in evidence.